2022
DOI: 10.1002/prp2.915
|View full text |Cite
|
Sign up to set email alerts
|

Impact of schizophrenia relapse definition on the comparative effectiveness of oral versus injectable antipsychotics: A systematic review and meta‐analysis of observational studies

Abstract: Although relapse is an important outcome to measure the effectiveness of schizophrenia treatment, no standard definition exists. This review aimed at identifying definitions and measurements of schizophrenia relapse in observational studies of long‐acting injectables (LAIs) versus oral antipsychotics (OAPs) and at determining their impact on heterogeneity of comparative effectiveness estimates. A systematic review was conducted using MEDLINE and Embase (01 January 2010–11 November 2019 [date last searched]). P… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(1 citation statement)
references
References 51 publications
(200 reference statements)
0
1
0
Order By: Relevance
“…Poor medication adherence is a common issue among schizophrenia patients, leading to poor clinical outcomes, including increased distress, relapse, rehospitalization, and increased rates of mortality and morbidity, as well as increased healthcare costs ( Chan et al, 2021 ; Cristarella et al, 2022 ). Studies have shown that individuals who do not adhere to their prescribed medication regimens are more likely to experience psychotic episodes, worsening symptoms, and functional impairment ( Llorca et al, 2018 ; Yang et al, 2021 ).…”
Section: Review Of Literaturementioning
confidence: 99%
“…Poor medication adherence is a common issue among schizophrenia patients, leading to poor clinical outcomes, including increased distress, relapse, rehospitalization, and increased rates of mortality and morbidity, as well as increased healthcare costs ( Chan et al, 2021 ; Cristarella et al, 2022 ). Studies have shown that individuals who do not adhere to their prescribed medication regimens are more likely to experience psychotic episodes, worsening symptoms, and functional impairment ( Llorca et al, 2018 ; Yang et al, 2021 ).…”
Section: Review Of Literaturementioning
confidence: 99%